2021
DOI: 10.1177/10732748211051228
|View full text |Cite
|
Sign up to set email alerts
|

Construction and Validation of a Novel Nomogram to Predict the Overall Survival of Patients With Combined Small Cell Lung Cancer: A Surveillance, Epidemiology, and End Results Population-Based Study

Abstract: Introduction Combined small cell lung cancer (C-SCLC) represents a rare subtype of all small cell lung cancer cases, with limited studies investigated its prognostic factors. The aim of this study was to construct a novel nomogram to predict the overall survival (OS) of patients with C-SCLC. Methods In this retrospective study, a total of 588 C-SCLC patients were selected from the Surveillance, Epidemiology, and End Results database. The univariate and multivariate Cox analyses were performed to identify optim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Nowadays, the nomogram is a widely used predictive tool to predict the survival probability of cancer patients ( 8 , 9 ). It could easily visualize the risk of each patient according to the contribution to the study outcome of variables in the multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, the nomogram is a widely used predictive tool to predict the survival probability of cancer patients ( 8 , 9 ). It could easily visualize the risk of each patient according to the contribution to the study outcome of variables in the multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Nomogram is a visual multivariate prognostic model that contains more predictors than traditional staging systems, thereby allowing individualized risk estimation. Previous publications revealed that nomogram has promising performance in predicting the survival probability of some malignancies compared to traditional TNM staging system (8,9). To our knowledge, several nomograms were developed to predict the recurrence risk of TETs in the past few years (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…Skrede et al used CNN algorithms to stratify CRC patients based on survival rate to identify those patients who would likely not benefit from adjuvant chemotherapy versus those patients who would require such treatment (76). Similarly, another CNN algorithm developed by Jiang et al could predict disease recurrence risk and overall survival for stage III CRC using gradient boosting (74). A CNN algorithm was also used to predict survival based on stromal microenvironment data obtained from HE slides (77).…”
Section: Prediction Of Patient Survivalmentioning
confidence: 99%
“…Prognostic predictors are valuable tools for treatment decision-making by helping clinicians choose the most suitable treatment modality for each patient ( 74 , 75 ). Survival prediction may be particularly valuable in early-stage CRC, as it can help clinicians decide whether adjuvant chemotherapy is suitable or not.…”
Section: Role Of Ai In Crc Prognosticationmentioning
confidence: 99%
See 1 more Smart Citation